EET-Hamming monocular high-speed measurement for long-span bridge structure displacement on a shaking table. (April 2023) - Liu, Xianglei; Jia, Zhenkai; Zhang, Pengfei; Chen, Yuxin; Li, Shenglong; Wang, Runjie
Highlights: A high-accuracy monocular high-speed measurement method for long-span bridge structure displacement. A monocular high-speed measurement method based on EET-Hamming is proposed, which is robust and efficient for long-span bridge structure displacements measurement without deploying artificial targets. Comparison experiments with high and low contrast targets are designed to verify the advantages of the proposed EET-Hamming method over other methods. The efficacy of the proposed EET-Hamming method has been validated through loading the bridge structure with two different seismic waves. Abstract: Monocular displacement measurement is widely used for the vibration monitoring of bridge structures on shaking tables. To efficiently and robustly measure the low-contrast targets obtained by a high-speed camera, this study proposes an EET-Hamming monocular high-speed measurement method. First, the EET and Otsu methods are combined to enhance and binarize the obtained image sequences, which can track the obtained low-contrast targets efficiently and robustly. Second, the minimum Hamming distance matching method is proposed to determine the similarity of the images and further improve the efficiency and accuracy of the image sequence processing. Finally, a nine-point least squares polynomial surface fitting method is proposed to calculate the sub-pixel displacement and convert them to the corresponding actual displacement. The results show that the proposed EET-Hamming monocular high-speed measurement method has a higher displacement measurement accuracy and processing efficiency.